Hole transport free flexible perovskite solar cells with cost-effective carbon electrodes. (18th December 2020) - Xie, Haixia; Yin, Xingtian; Guo, Yuxiao; Liu, Dan; Liang, Tong; Wang, Gangfeng; Que, Wenxiu
Abstract: Low temperature derived carbon electrodes are employed to fabricate low cost hole transport layer free perovskite solar cells, in which perovskite films annealed in glovebox and ambient air are used as the absorbers, respectively. Results suggest that the air annealed sample has bigger crystal grains and higher crystallinity, and the existence of a small amount of lead iodide which passivates grain boundaries contributes to a lower trap density. As a result, a maximum power conversion efficiency (PCE) of 13.07% was obtained on the air annealed device, which is higher than those of devices annealed in glovebox (11.25%). Furthermore, the stability of unencapsulated devices stored in wet (with humidity around 90% ± 5%) air atmosphere are investigated and the results prove that our devices exhibit good stability. In addition to rigid devices, flexible perovskite solar cells are also fabricated using the same procedure. The highest PCE of 11.53% is demonstrated on the champion flexible device, and 69% of its initial PCE can be maintained even after 2000 bending cycles with a bending radius of 2 mm. Our work provides a promising and simple rout for low-cost, air-stable, high-efficiency carbon perovskite solar cells for both large area production and flexible electronic devices industry.